The Maastricht Inflation Criterion : How Unpleasant Is Purgatory? - Bulir, Ales (IMF Working Papers; Working Paper ;, 2006)
The Maastricht inflation criterion, designed in the early 1990s to bring "high-inflation" EU countries in line with "low-inflation" countries prior to the introduction of the euro, poses challenges for both new EU member countries and the European Central Bank. While the criterion has positively influenced the public stance toward low inflation, it has biased the choice of the disinflation strategy toward short-run, fiat measures-rather than adopting structural reforms with longer-term benefits-with unpleasant consequences for the efficiency of the eurozone transmission mechanism. The criterion is also unnecessarily tight for new member countries as it mainly reflects cyclical developments.